The Potential of Sustainable Palm Oil Downstream to Improve the Green Economy of the Community - Julia Julia; Darman Saputra; Hamsani Hamsani; Dian Prihardini Wibawa (Goodwood Publishing, 2026)
Purpose: This study analyzes the transformation of the green economy in the downstream oil palm industry in Bangka Belitung Islands Province, focusing on how downstreaming, technological innovation, and government policies can accelerate the shift from a resource-based economy to a high-value, low-carbon economy. Research Methodology: A mixed-methods design was used, with quantitative panel data from 2014–2024 (33 observations from three districts) analyzed using the Fixed Effect Model (FEM). Qualitative data was gathered through in-depth interviews with 35 stakeholders from industry, government, and farming sectors. Results: The study finds that palm oil down streaming, technological innovation, and government policies positively and significantly strengthen the green economy. The green economy plays a mediating role in transitioning to the